Challenges in Process Dissociation Measures for Moral Cognition - Kunnari, Anton; Sundvall, Jukka R. I.; Laakasuo, Michael (Frontiers in Psychology, 2020)
The process dissociation (PDP) procedure for moral cognition was created to separately measure two dispositions of moral judgment based on the dual-process theory of moral reasoning: deontological and utilitarian inclinations. In this paper we raise some concerns from a psychometrics perspective regarding the structure, reliability, and validity of the moral PDP as measures of individual differences. Using two simulation studies as well as a real sample of N = 1010, we investigate the psychometric properties of the moral PDP. We present novel evidence showing that 1) some correlations between PDP parameters are mathematical artefacts, and as such cannot be taken as evidence in support of a theory, 2) there are severe response inconsistencies within dilemma batteries, and 3) reliability estimates for these scores seem to be far below the accepted standards. We discuss some potential theoretical and content-related reasons for these statistical issues and their implications. We conclude that in their current form, PDP measures of utilitarian and deontological tendencies are sub-optimal for assessing individual differences.